VIDEO MAPPING AS AN ARTÍSTIC EXPRESSION IN THE ENHANCEMENT OF BUILDINGS OF HISTORICAL AND HERITAGE INTEREST, AYSÉN REGION, CHILE (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
This work details the lighting intervention through the video mapping technique in nine self-built vernacular buildings in the region of Aysén, Chile. This exercise shows the importance of the visual arts as an indispensable resource and as a useful tool for the analysis of the different problems of the past, and its results tend to generate a new moment of cultural appropriation by its inhabitants and surrounding communities, and a greater recognition by the governmental public institution, the academy and the international community.
Keywords: Video mapping; vernacular architecture; contemporary art; Aysén region; Chili